The Need for Diffraction in STEM -fields: An Ethical Feminist Consideration of the Concept of Genderscripting - Grewe, Felix (Feminist Encounters Special Issue on Peripheral Visions of Alternative Futures: Feminist Techno-imaginaries)

Vernetzte Musikquellen des 19. Jahrhunderts. Überlegungen zum Zusammenspiel wissenschaftlicher Editionen mit RISM am Beispiel des Stuttgarter Faust 1832 - Frömmel, Lena; Münzmay, Andreas (Musikquellen des 19. Jahrhunderts in Deutschland. Herausforderungen und Chancen)
This article explores the challenges and opportunities of documenting and cataloguing 19th-century music sources in Germany, using the 1832 Stuttgart production of Goethe’s Faust with music by Peter Joseph von Lindpaintner as a case study. The main focus lies on the potential interplay between (digital) critical music editions and RISM as complementary approaches to source documentation. While RISM has traditionally concentrated on pre-1800 sources, the vast and complex landscape of 19th-century music-theatrical materials—especially handwritten performance materials, but also printed sources—calls for new collaborative strategies. Drawing on the Faust edition within the OPEN Edirom project, which publishes data in open, structured formats (TEI and MEI) and makes them accessible via the RADAR4Culture repository and the Culture Knowledge Graph, the article argues for closer integration between editorial projects and RISM through stable identifiers and Linked Open Data principles. Editorial descriptions do not compete with RISM records but meaningfully extend them, and vice versa. The case study illustrates how editorial source descriptions and full-text editions could enhance the informational scope and augment the reach of RISM, and how RISM could serve as a basis for more granular, interconnected, and FAIR-compliant musicological research infrastructures. The article proposes RISM as a central access point for distributed research data and outlines the simple yet effective steps researchers can take to enhance discoverability and interoperability: namely, by using (or if necessary, creating) RISM IDs and by publishing data with persistent Digital Object Identifiers (DOIs).

Peter Joseph von Lindpaintner, Ouverture, Entreacte, Chöre und Lieder zu Goethes Faust nach der szenischen Einrichtung von Carl Seydelmann (1832)
The present OPEN Edirom digital edition of Goethe’s Faust presents the literary and musical text of the work as it was possibly performed at its premiere (Friday, March 2, 1832) and consecutive performances under the direction and participation of Carl Seydelmann (directing the production and playing the role of Mephistopheles) and Peter Joseph von Lindpainter in the Stuttgart Hoftheater in 1832 (March 11, May 28, October 12) and 1833 (May 14, December 27), in accordance with the surviving sources, i.e., the original theatre material preserved in the Württemberg State Library in Stuttgart (D-Sl). This material constitutes a nearly complete autograph source package consisting of text adaptation (an autograph by Seydelmann incorporated into a copy of the print edition published by Cotta in Tübingen in 1830) and corresponding music (two volumes with autograph scores by Lindpaintner).

Mit KI (Elicit) den Forschungsstand beschreiben – ein kritischer Erfahrungsbericht - Schmidt, Rebecca (Sozialwissenschaftliche Methodenberatung)

Participatory Research with Teachers - A Critical Analysis of Power Dynamics - Schmidt, Rebecca (Transdisziplinäre Räume in den Kulturwissenschaften)

Wild bonobos experience unusually low bone resorption during early lactation relative to humans and other mammals - Behringer, Verena; Sonnweber, Ruth; Fruth, Barbara; Housman, Genevieve; Douglas, Pamela Heidi; Stevens, Jeroen M. G.; Hohmann, Gottfried; Kivell, Tracy L. (Evolutionary Human Sciences)
In mammals, pregnancy and lactation are marked by calcium stress and bone resorption, leading to reduced bone mineral density. In humans, these periods may partly explain the higher prevalence of osteoporosis in older women compared with men, but lactation patterns in modern humans may reflect cultural influences rather than natural conditions. The extent to which these findings apply to wild-living mammals remains unknown. We measured urinary C-terminal crosslinking telopeptide of Type I collagen (CTX-I) levels, a bone resorption marker, during pregnancy in wild and zoo-housed bonobos (Pan paniscus) and during lactation in wild bonobos. Studying wild-living primates such as bonobos can provide insights into ancestral reproductive adaptations. We found an increase in CTX-I levels towards the end of pregnancy in zoo-housed and primiparous wild females. Contrary to expectations, CTX-I levels during early lactation are lower than in other reproductive phases. This pattern diverges from the assumption that lactation increases bone resorption. Our findings suggest that wild bonobos may use physiological or behavioral strategies to modulate bone metabolism during lactation. These adaptations, shaped in natural environments, provide insight into evolutionary pressures on skeletal health and may inform strategies to mitigate bone loss in humans.
Keywords: Reproductive phase; Hominoid; CTX-I; Bone turnover markers; Pan paniscus; Bone density

Doing Gender Reflexionen im Lehramtsstudium - Steinhardt, Isabel (Förderung von Genderkompetenz in der Ausbildung von Lehrkräften)
Damit sich Lehramtsstudierende Genderkompetenz im Studium aneignen können, ist es zunächst notwendig, diese zur Reflexion über Gender anzuregen – so die These dieses Beitrags. Kompetenzen entstehen durch die Aneignung von Kenntnissen, Fähigkeiten, Fertigkeiten und Werthaltungen und sind an Sozialisationserfahrungen und damit inkorporierte Handlungsweisen und Normen gebunden Genderkompetenz ist notwendig, um Schülerinnen und Schülern gleiche Entwicklungschancen jenseits geschlechtsspezifischer Zuschreibungen zu ermöglichen und bei angehenden Lehrkräften umfassende Genderkompetenz zu etablieren. Dabei ist Gender sozial konstruiert, was als „doing gender“ bezeichnet wird. Der vorliegende Beitrag stellt ein Seminarkonzept vor, in dem über den Doing-Gender-Ansatz die alltägliche Herstellung von Geschlecht in den Mittelpunkt gerückt wird. Erst wenn – so die Grundannahme des Beitrags – verstanden ist, wie Geschlecht in der Gesellschaft über das Doing Gender (re)produziert wird, kann das Doing durch eigene Verhaltensänderungen verändert werden. Wie dies erreicht werden kann, wird im Folgenden dargestellt. Dazu wird zunächst das Seminarkonzept vorgestellt, in dem durch die Reflexion einer schulischen Situation, in die die Studierenden selbst involviert waren, das Doing Gender aufgedeckt wird. Anschließend wird eine Typologie von Situationen vorgestellt, die auf den Portfolios von fünf Seminaren (WS 21/22bis WS 23/24) basiert. Abschließend wird evaluiert, inwieweit ein Kompetenzerwerb in Bezug auf Gender im Seminar stattgefunden hat.
Keywords: Doing Gender; Lehramt; Kompetenzen

Intra-individual variability in TVA attentional capacity and weight distribution: A reanalysis across days and an experiment within-day - Banh, Ngoc Chi; Scharlau, Ingrid
The present article offers an assessment of intra-individual variability in visualattention using the Theory of Visual Attention, which provides a formal framework forquantifying attentional components. We specifically investigated overall attentionalcapacity – that is, the available processing speed – and its distribution, the relativeattentional weight.By reanalyzing a large existing dataset from Tünnermann and Scharlau (2021),we found that across multiple testing days, participants either remained stable within a20 Hz margin or showed consistent improvements in capacity – in some cases triplingtheir initial capacity. The weights in response to salient stimuli were remarkablyconsistent.To determine whether increases in capacity reflect pure test-retest effects or arefacilitated by consolidation between days, and to quantify within-day variability, weconducted a second study in which participants completed five self-administeredsessions within a single day. Capacities remained within the same magnitude and didnot show a consistent directional trend. The relative weights exhibited comparativelylittle variation in most participants, akin to the previously analyzed dataset. Further,estimation uncertainty increased with higher capacity values.These results suggest that capacity may be subject to training effects, but thatsuch improvements appear to depend on longer breaks between sessions. This hasimportant implications for individualized assessment: A personal prior could beestimated from a single session to accelerate future estimations, as long as subsequentsessions occur on the same day. Participants with higher capacities may require tailoredexperimentation methods when small to medium effects are of interest, due to increaseduncertainty.

Bernd Schröder: Religionspädagogische Ökumenik. Weltweites polyzentrisch-plurales Christentum als Bildungsreligion, Tübingen 2025 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

"Seine besondere Chance ist, dass er sterben kann." (Helmut Simon) Verausgabung, Popkulur und Erneuerung als grundlegende Dimensionen des Kirchentags - Schroeter-Wittke, Harald (Pastoraltheologie)

Künstliche Intelligenz und professionsbezogene Aufgaben von Lehrkräften - Herzig, Bardo (SchulVerwaltung NRW)

Enhancing Pre-Service Teachers' Reflective Competence Through Structured Video Annotation - Rogge, Tim; Herzig, Bardo (education sciences)

Émilie Du Châtelet on Time - Hagengruber, Ruth Edith (The Routledge Companion to Philosophy of Time)

Die (produktive) Rolle von generativer KI im erziehungswissenschaftlichen Diskurs - Herzig, Bardo (Erziehungswissenschaft. Mitteilungen der Deutschen Gesellschaft für Erziehungswissenschaft. Erziehungswissenschaft nach ChatGPT)

Künstliche Intelligenz und professionsbezogene Aufgaben von Lehrkräften - Herzig, Bardo (SchulVerwaltung Bayern)

Team-Teaching angehender Lehrkräfte und Kompetenzen von Kindern im inklusiven naturwissenschaftlichen Sachunterricht. Vortrag auf der Tagung der Kommission „Grundschulforschung und Pädagogik der Primarstufe“, Sektion Schulpädagogik, Deutsche Gesellschaft für Erziehungswissenschaft (DGfE). Thema: „Bildung ohne Grenzen denken. Visionen der Grundschulbildung im europäischen Raum" - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Einstellungen und prosoziales Verhalten von Grundschulkindern gegenüber Peers mit emotional-sozialem Förderbedarf im inklusiven Unterricht. Vortrag auf der Tagung der Kommission „Grundschulforschung und Pädagogik der Primarstufe“, Sektion Schulpädagogik, Deutsche Gesellschaft für Erziehungswissenschaft (DGfE). Thema: „Bildung ohne Grenzen denken. Visionen der Grundschulbildung im europäischen Raum" - Löper, Marwin Felix; Hellmich, Frank

Exploring primary school teachers’ and special education teachers’ self-efficacy beliefs concerning inclusive education: A qualitative study. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Finke, Pauline; Schulze, Jan Roland; Hellmich, Frank

The role of teacher feedback for primary school students’ motivation and mathematical competencies. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Finke, Nils; Knickenberg, Margarita; Hellmich, Frank

Pre-service teachers’ professional self-concept development concerning team-teaching in primary schools. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Schulze, Jan Roland; Hellmich, Frank